Guru Granth Sahib in the Writings of Western Women. Issue 1 (15th September 2020) - Nesbitt, Eleanor
Abstract : The Guru Granth Sahib is, in Sikh belief, the scripture that embodies their living Guru. Although major anthologists of western writers on Sikhs and their religious tradition have hardly noticed many European and North American women's observations and comments, Sikhs and their scripture have featured in the travelogues and novels, journals, memoirs and monographs written by western women who were neither converts to Sikhism nor academics in the modern sense. Many of these women described the prominence and honouring of the Sikhs' scripture, Guru Granth Sahib in the gurdwaras that they visited, some mentioned its role in life cycle rites, and some wrote about the content of Sikh scripture. For this they relied on (male) translators. In the context of their own Christian religious background and intellectual journeys, this paper examines the responses of western women to both the physical presence and the content of the Guru Granth Sahib, including Annie Besant's understanding of Guru Nanak as a populariser of Vedanta.